India monocracy - Singh, Joginder (New Delhi, 2007)
If men were angels, no government would be required. If angels were to governmen, neither external nor internal controls on government would be needed. But since human beings are governing and no human beign is without infirmities, aberrations and that also serious aberrations take place. Despite the brought spots and the country doin well, and economy booming at least for the richer and middle class, things for a vast majority are far from rosy. Our country is pasing through vitalizing and bristling times. The present descriptionn almost fits the current epoch in India, what Charles Dickens once said; 'It was the best of times, it was the worst of times, it was the age of foolishness... it was the spring of hope, it was the winter of despair .... in short, the period was so far like the present period..." This book is a journey through such times, lived in not only by the author, but his generations. Every book is written with an objective, which in this case, being to involve the rulers and ruled in good governance. Good or bad govermance affects us all. In the case of some, it is smaller degrees, and in the case of others larger degrees. History does not long assign the care of freedom th the weak or the timid. Both the past and future will always belong to the bold and brave. Let us be clear on one fact that it is not for the government to keep the citizen from falling into error. No Government does it. On the contrary, it is the job of the citizen to keep the government from falling into error.This book seeks to examine and raise some of the issues, facting the Nation, Government and Citizens, so that the citizenes should at least get the fruits of democracy. Agreed, that it is not the best form of Government, but unfortunately, all those tried before, have proved worse.
Keywords: Terrorism